The Effect of the Direct Observation Method on Seventh-Grade Students’ Descriptive Text-Writing Ability at SMPN 2 Nainggolan in the 2024/2025 Academic Year - Sitinjak, Febriartha; Simaremare, Juni Agus; Saragih, Elza Leyli Lisnora (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2025)
This study addresses the persistent challenge of low descriptive text writing ability among seventh-grade students, which is largely attributed to conventional teaching methods that lack authentic experiential engagement. The research aimed to evaluate the impact of implementing the Direct Observation Method on students’ descriptive writing proficiency. Using a one-group pretest–posttest design, 30 seventh-grade students from SMPN 2 Nainggolan were selected through cluster random sampling. Data were collected using a performance test scored with a validated rubric based on Nurgiyantoro’s framework. Statistical analysis employing a paired-samples t-test revealed a significant improvement in students’ writing performance (t observed = 7.677 > t critical = 1.699), with mean scores increasing from 54.33 (Very Poor) to 77.83 (Good), representing a 23.50-point gain. The method showed its strongest effects on content development (+8.1 points) and organization (+6.3 points), while linguistic aspects exhibited more moderate improvement. These findings indicate that direct environmental engagement substantially enhances students’ ability to generate and organize descriptive content and offer educators a practical strategy for bridging the gap between theoretical instruction and authentic writing experiences in descriptive text composition.